Not Quite Monoracial: Biracial Stereotypes Explored. (March 2020) - Skinner, Allison L.; Perry, Sylvia P.; Gaither, Sarah
Stereotypes often guide our perceptions of members of social groups. However, research has yet to document what stereotypes may exist for the fastest growing youth demographic in the United States—biracial individuals. Across seven studies ( N = 1, 104), we investigate what stereotypes are attributed to various biracial groups, whether biracial individuals are stereotyped as more similar to their lower status monoracial parent group (trait hypodescent), and whether contact moderates these stereotypes. Results provide evidence of some universal biracial stereotypes that are applied to all biracial groups: attractive and not fitting in or belonging. We also find that all biracial groups are attributed a number of unique stereotypes (i.e., which are not associated with their monoracial parent groups). However, across all studies, we find little evidence of trait hypodescent and no evidence that the tendency to engage in trait hypodescent varies as a function of contact.